Determinants of Fraud Prevention in Surakarta City Government - Krisnandya Purna Febiyuantama; Evi Maria (Postgraduate Program Merdeka University, 2024)
This research aims to find empirical evidence of the relationship between the government's internal control system, compliance with accounting rules, and fraud prevention in the Surakarta City government. Primary data was collected using a questionnaire. The total sample for this research was 120 employees of the Finance Department of the Regional Office of Surakarta City, spread across30 Regional Apparatus Organizations. Data were analyzed using multiple regression analysis. The research results found that the government's internal control system and compliance with accounting rules positively affected fraud prevention in the Surakarta City government. Additional testing by adding educational level and background as control variables provides consistent findings that the internal control system and compliance with accounting rules positively affect fraud prevention. In contrast, academic level and background do not affect fraud prevention. These findings confirm that the Surakarta City government's success in suppressing fraud cases in the area is because it has an excellent internal control system and adheres to accounting rulesDOI: https://doi.org/10.26905/afr.v7i1.11902